Modelo de inserção de nova arquitetura em áreas urbanas diferenciadas : experimentação na cidade de Sabará/MG - Silva, Jaqueline Pugnal da (2012)
The discussion about the pair of themes Old / New, opened in the fifth century, when the word appears modern, being used to mean "now, recently," presenting itself as an attempt to establish the distinction between his contemporaries, indicating no privil